2013
DOI: 10.2217/fca.13.12
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure and Iron Deficiency Anemia in Italy: Results From CARMES-1 Registry

Abstract: In HF patients, there is poor attention paid to anemia, its causes and treatment. Current iron deficiency treatment strategies are mismanaged and CARMES-1 demonstrated that they appear to be insufficient at improving patient outcome in terms of rehospitalization rate reduction, generating high costs, which could be avoided through an optimized treatment strategy. Therefore, more efficacious, efficient and cost-effective treatment strategies are required in Italy for HF patients with iron deficiency anemia to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
4
5
0
Order By: Relevance
“…Despite such guidelines we recently found that only 19.7% of patients admitted to our hospital with a primary diagnosis of HF had their iron parameters measured, yet in those in whom it was measured, 80% were found to be iron deficient [ 43 , 44 ]. A similar lack of investigation and treatment of ID in HF has been found by others [ 45 , 46 ].…”
Section: Official Recommendations For the Diagnosis And Treatment supporting
confidence: 72%
See 1 more Smart Citation
“…Despite such guidelines we recently found that only 19.7% of patients admitted to our hospital with a primary diagnosis of HF had their iron parameters measured, yet in those in whom it was measured, 80% were found to be iron deficient [ 43 , 44 ]. A similar lack of investigation and treatment of ID in HF has been found by others [ 45 , 46 ].…”
Section: Official Recommendations For the Diagnosis And Treatment supporting
confidence: 72%
“…Non anemic iron deficiency is very common [ 121 , 122 ]. It may be a major cause of symptoms as shown above but is often missed [ 43 , 44 , 45 , 46 , 112 , 122 ]. Health personnel are apparently often not aware of the presence and importance of ID without anemia [ 122 ] and should be made aware of this very common entity.…”
Section: Lack Of Awareness Of the Importance On Non-anemic Iron Dmentioning
confidence: 99%
“…Previous studies reported that 17-57% of patients admitted with HF had anemia (Horwich et al 2002;Ezekowitz et al 2003;Hamaguchi et al 2009;Caira et al 2013). In the present clinical study, the observed rate of anemia in consecutive HF patients admitted to the Cardiovascular Disease Department of Niigata University Medical and Dental Hospital was 41%, which agreed with the previous reports.…”
Section: Anemia and Hepcidin In Hf Patientssupporting
confidence: 92%
“…These real word data, that confirm the results of our CARMES 1 study in a cohort of 418 hospitalized HF patients in Italy in which ID was underdiagnosed and undertreated [39] ( Figure 9), underline that diagnostic and therapeutic efforts on ID management in HF are still low in clinical practice.…”
Section: Iron Deficiency Anemiasupporting
confidence: 80%